Lactic acid fermentation from tapioca starch by lactobacillus casei TISTR 453 using simultaneous saccharification and fermentation process - Adthalungrong, Chaowaree; Saechua, Nidarat; Doungkaew, Kasara (Asia-Pacific Journal of Science and Technology, 2017)
Lactic acid and its derivatives have wide applications in various industries. One of the most interesting applications of lactic acid is to serve as a monomer for polylactide synthesis. In the current research, lactic acid production from tapioca starch by lactic acid bacterium, Lactobacillus casei TISTR 453, was studied using a simultaneous saccharification and fermentation process. We focused on investigating optimum temperature and medium compositions. Tapioca starch was supplied at 150 g/L and starch hydrolysis was initiated by the addition of 0.10 % (v/starch wt.) - amylase. Subsequently, liquefied starch was used to prepare a fermentation medium (modified MRS formula). Afterwards, 0.10% (v/starch wt.) glucoamylase as well as lactic acid starter at 10 6 CFU/ml were simultaneously induced and lactic acid fermentation was allowed for 72 h. The results revealed that 40 C was an optimum temperature. For the optimization of glucoamylase and medium compositions when response surface methodology (RSM) with centrl composite design (CCD) was employed, the results suggested that 0.10% (v/starch wt.) glucoamylase, 87.5 g/L calcium carbonate, and 10.0 g/L yeast extract were optimal. The model generated from RSM showed a predicted lactic acid concentration at 131.50 g/L when fermentation was conducted using Lb. casei TISTR 453 with the optimized medium and incubated at 40 C for 48 h. Eventually, the results were validated using the optimized medium resulting in 130 g/L lactic acid, which corresponds to 0.87 g lactic acid/g starch.